Enteral versus intravenous antibiotics for critically ill patients: A pilot study - Dayana dos Santos Oliveira; Julia Vitória da Rocha; Juliano Gasparetto; Carolina Hikari Yamada; Joao Paulo Telles; Felipe Francisco Tuon (Brazilian Journal of Infectious Diseases, 2025)
Background: While there are valid concerns regarding the use of Enteral Antibiotics (EN) in the Intensive Care Unit (ICU), the evidence opposing this practice has not been thoroughly evaluated in prior research. Aim: This study aimed to evaluate the transition from sequential Intravenous (IV) antibiotics to EN antibiotics in critically ill patients with infections. Methods: This was a prospective, multicenter, randomized, unblinded clinical trial involving patients with infections who received antibiotic therapy. The study compared sequential IV antibiotic treatment to EN therapy in patients who continued standard IV therapy in the intensive care unit. Primary outcome measures included mortality and clinical improvement assessed on days 3, 5, and 10. Secondary outcomes encompassed hospital and ICU length of stay, costs, and evaluation of microbiological failure. Results: A total of67 patients were included in the EN group and 60 patients in the IV group. Most patients were classified as infected (66.1 %), with 33.1 % diagnosed with sepsis. In-hospital mortality rates were comparable between the two groups, with 31 % in the EN group and 30 % in the IV group. Clinical outcomes assessed on days 3, 5, and 10 showed no significant differences between the groups. Among the 67 patients in the EN group, 7 (10.5 %) required a return to intravenous antibiotic therapy. Notably, drug costs in the IV group increased by 207 %. Conclusion: This is the first controlled and randomized study to evaluate the oral/enteral route of antibiotic administration in the ICU. The findings indicate no significant differences in clinical outcomes or survival rates between the two groups, while demonstrating reduced costs and comparable safety with EN antibiotics.